A systematic search and appraisal of intervention characteristics used to develop varied communication functions in children with autism who use aided AAC. (February 2022) - Logan, Kristy; Iacono, Teresa; Trembath, David
Highlights: AAC interventions varied in terms of strategies employed and dosage. Children with ASD learned to use a range of communicative functions via AAC. Diverse functions were most frequently taught using time delay and prompting. Individualising strategies, dosage, and setting may optimise outcomes. Abstract: Background: Aided augmentative and alternative communication (AAC) interventions have been shown to be effective in teaching children with autism spectrum disorder (ASD) to communicate for a range of communication functions. However, currently little is known about the specific characteristics of interventions that can be used to teach functions other than object request. Method: A systematic search and appraisal was undertaken of extant ASD-AAC research to determine whether outcomes varied according to intervention strategies used, communication functions and behaviours targeted, treatment intensity, and participant characteristics. Eighteen studies were identified and appraised for constituents and outcomes. Results: Intervention components varied widely, as did behaviours targeted, participant characteristics, dosage, and outcomes. There was evidence that a range of functions and communication behaviours could be taught successfully in structured, context-bound routines, with the teaching strategies of time delay and prompting applied most frequently. A small correlation was found between dosage and effect size. Conclusions: The current appraisal provides evidence that children with ASD who use aided AAC can learn communication functions beyond making requests for objects. AAC interventions that include time delay and prompting, and that teach skills in specific routines, are more likely to demonstrate a moderate to large effect size. Further research on the range of factors that may potentially influence outcomes, such as participant characteristics and dosage, is needed.